Ketersediaan Fitur Sebagai Pemoderasi Pengaruh Persepsi Kepercayaan dan Persepsi Manfaat terhadap Penggunaan Digital Banking - Nurliza Lubis; Ainul Yusna Harahap; Syardiansah Syardiansah (Mahesa Research Center, 2023)
The discussion in this study is about customer perceptions of using digital banking after the COVID-19 pandemic. The implications of the research are the availability of features as a moderator of the influence of perceived trust and perceived benefits on the use of digital banking after the COVID-19 pandemic. The population used in this research were PT Bank Syariah Indonesia (Bank BSI) KCP Padang Bulan Medan customers. A total of 102 respondents were selected based on multivariate analysis. The data obtained were processed using SPSS 23. The research methods used were the Instrument Test, Classical Assumption Test, and Hypothesis Test. This research shows that perceptions of trust do not influence the use of digital banking after the Covid-19 pandemic. Meanwhile, perceived benefits influence digital banking after the Covid-19 pandemic. The availability of features also makes it easier to interact between trust and benefits of using digital banking after the Covid-19 pandemic. For further discussion, you can use an expanded research sample and explore other variables to assess customer perceptions of digital banking.